Alvar Aalto estudo do processo projetual. Beleza e funcionalidade em Arquitetura - Ana Mafalda Ribeiro Silva Marques (2021)
Drawn upon the housing issue, the urgency of studying the basic human needs - in reconciliation with nature - is exposed: not as a mere stylistic problem, but as a socially responsible task. Presenting his architectural work as one that actively promotes continuous development and transformation, Alvar Aalto expresses the need within Architecture of attending to the Modern Man's physical and intellectual needs. In the beginning of the century, amidst full European background, his approach to Rationalism and Functionalism has prioritized the Human element in the architect's practice, bringing to light new ways in which Social-Cultural significance can be promoted in the long-run. This essay dwells on the concepts of beauty and functionality in Architecture, calling upon the oeuvre and project process of the Finnish architect Alvar Aalto. Addressing the period between 1920-1950, it centers its focus on the housing projects - Villa Flora (1926-1938), Casa-Atelier (1935), Casa Experimental (1952) and Villa Mairea (1938-39) - and the Paris (1937) and New York (1939) exhibition halls, to cross-examine its methods of writing, projecting and building the works. In the hopes of presenting the Architecture phenomena under a Humanist perspective, here we find the human housing process, as described by Hans van der Laan, the problematics of beauty and functionality through the project method of Álvaro Siza, and the relationship between the Artificial and the Natural as proposed by Gilles Clément. Making this theoretical referencial our starting point, we were able to trace some motifs - Function, Form, Wall - that pave the way throughout the paper to considerations within the study of this houses. Following the theoretical component of Alvar Aalto, the essay deconstructs the idea of Humanizing Architecture, at the heart of the Architect's work. In searching for the harmony in each and every detail, beauty and functionality link deeply with one another when approaching themselves to the essence of the architectural object. Aalto reminds us of the vast potentialities that were brought to us by technological development, nurturing the idea of a New Renaissance in Finland, facing the social paradigm where his country stands. Striving to incorporate the human craft into the natural space, Aalto tries to fuse his functionalist approach with the sentiment of nacional identity, as a means of promoting culture within his works. The substance behind the architectonic shapes he chooses is the struggle to answer the physical and intellectual needs of the human way of living, in harmony with its natural surroundings - laying out the intrinsic relations between interior and exterior spaces. At the crossing-point of his theoretical-practical work, one could single out the Architectonic Anarchism principle, as exposed by Schildt, making reference to the social ideology reflected throughout Aalto's creative process. Lastly, it will be rendered a reflection on one very peculiar space belonging to the Faculdade de Arquitetura da Universidade do Porto, where it will be called into question the presumable influence of Aalto's thought within the project of Álvaro Siza. This last section of the essay attempts to establish an acknowledgment of the importance of the dwelling as such, and as a fundamental part of the academic path of FAUP's community.